Secure Information Transmission Device Implemented on an Embedded System using 3DES and AES Algorithms - Martínez Santa, Ricardo; Martínez Santa, Fernando; Montiel Ariza, Holman (International Journal of Engineering Research and Technology, 2020)
The main objective of this article is to implement a hardware-software prototype for sending and receiving secure information between a PC and an embedded system, using cryptographic algorithms 3DES (Triple DES) and 3 different versions of AES. Likewise, a comparative study is carried out between the implemented algorithms, in terms of the execution times of the encryption and decryption operations, both in the PC and in the embedded system, in order to select the cryptographic algorithm that shows the best performance measures. Finally, it is determined that the algorithm with the best relation between total execution time and security level is the AES128, this having a much lower execution time in the implementation carried out in the PSoC 6 embedded system than in the PC. However, the implementation of the 196-bit and 256-bit versions of the AES algorithm can be done without significantly increasing the total algorithm execution time on both devices.
Keywords: 3DES; AES; cryptography; embedded systems; Scopus